Corporate Social Responsibility Mandatory Disclosure: The Effect on Firm Performance - Helmy Sukiswo; Rizdina Azmiyanti; Warsame Abdiaziz Hassan (Future Science, 2021)
The study aims to analyze the effect of corporate social reporting (CSR) mandatory disclosure on firm performance. This study uses a literature review with five selected articles. The data collection method uses several keywords related to the topic. Several proxies are used to measure firm performance. The result shows that the regulation of mandatory disclosure cannot affect firm performance at all. The different proxies can be one of the factors for a different result. In India, there are two different results even though the regulation has been implemented a few years ago. It indicates the need for the government to explain more about the new regulation because, at some point, companies are confused to apply the new regulation. In China, the studies proved that corporate social responsibility in mandatory disclosure is significantly affect the firm’s performance. In this case, it is mentioned that the awareness of companies in China can be classified good to understand the regulation. For further research, governement involvement can be added to test the effect.